Using Telerehabilitation to Deliver a Home Exercise Program to Youth With Arthrogryposis: Single Cohort Pilot Study - Marianne Gagnon; Gabriela Marino Merlo; Rita Yap; Jessica Collins; Caroline Elfassy; Bonita Sawatzky; Jacquelyn Marsh; Reggie Hamdy; Louis-Nicolas Veilleux; Noémi Dahan-Oliel (JMIR Publications, 2021)
BackgroundArthrogryposis multiplex congenita (AMC) is characterized by joint contractures and muscle weakness, which limit daily activities. Youths with AMC require frequent physical therapeutic follow-ups to limit the recurrence of contractures and maintain range of motion (ROM) and muscle strength; however, access to specialized care may be limited because of geographical distance. Telerehabilitation can offer a potential solution for delivering frequent follow-ups for youth with AMC, but research on the use of telerehabilitation in children with musculoskeletal disorders is scarce. ObjectiveThe study aims to evaluate the feasibility of delivering a home exercise program (HEP) by using telerehabilitation for youth with AMC. We also aim to explore the effectiveness of the HEP as a secondary aim. MethodsYouths aged between 8 and 21 years with AMC were recruited at the Shriners Hospitals for Children-Canada. The participants completed baseline and post-HEP questionnaires (the Physical Activity Questionnaire for Adolescents, Pediatrics Outcomes Data Collection Instrument, and Adolescent and Pediatric Pain Tool), and clinicians assessed their active ROM using a virtual goniometer. Clinicians used the Goal Attainment Scale with the participants to identify individualized goals to develop a 12-week HEP and assess the achievement of these goals. Follow-ups were conducted every 3 weeks to adjust the HEP. Data on withdrawal rates and compliance to the HEP and follow-ups were collected to assess the feasibility of this approach. The interrater reliability of using a virtual goniometer was assessed using the intraclass correlation coefficient and associated 95% CI. Nonparametric tests were used to evaluate feasibility and explore the effectiveness of the HEP. ResultsOf the 11 youths who were recruited, 7 (median age: 16.9 years) completed the HEP. Of the 47 appointments scheduled, 5 had to be rescheduled in ≤24 hours. The participants performed their HEP 2.04 times per week (95% CI 1.25-4.08) and reported good satisfaction with the approach. A general intraclass correlation coefficient of 0.985 (95% CI 0.980-0.989) was found for the web-based ROM measurement. Individualized goals were related to pain management; endurance in writing, standing, or walking; sports; and daily activities. In total, 12 of the 15 goals set with the participants were achieved. Statistically significant improvements were observed in the pain and comfort domain of the Pediatrics Outcomes Data Collection Instrument (preintervention: median 71; 95% CI 34-100; postintervention: median 85; 95% CI 49-100; P=.08) and Physical Activity Questionnaire for Adolescents (preintervention: median 1.62; 95% CI 1.00-2.82; postintervention: median 2.32; 95% CI 1.00-3.45; P=.046). ConclusionsThe remote delivery of an HEP for youth with AMC is feasible. Promising results were found for the effectiveness of the HEP in helping youths with AMC to achieve their goals. The next step will be to assess the effectiveness of this exercise intervention in a randomized controlled trial. International Registered Report Identifier (IRRID)RR2-10.2196/18688